Curcumin in Osteosarcoma Therapy: Combining With Immunotherapy, Chemotherapeutics, Bone Tissue Engineering Materials and Potential Synergism With Photodynamic Therapy - Xu, Chunfeng; Wang, Mingjie; Guo, Wei; Sun, Wei; Liu, Yuelian (Frontiers in Oncology, 2021)
Osteosarcoma is a dominating bone malignant tumor with high mortality due to pulmonary metastases. Furthermore, because of the cancer cell erosion and surgery resection, osteosarcoma always causes bone defects, which means dysfunction and disfigurement are seldom inevitable. Although various advanced treatments (e.g. chemotherapy, immunotherapy, radiotherapy) are coming up, the 5-year survival rate for osteosarcoma with metastases is still dismal. In line with this, the more potent treatments for osteosarcoma are in high demand. Curcumin, a perennial herb, has been reportedly applied in the therapy of various types of tumors via different mechanisms. In vitro, it has also been reported that curcumin can inhibit the proliferation of osteosarcoma cell lines and can be used to repair bone defects. This seems curcumin is a promising candidate in osteosarcoma treatment. However, due to its congenital property like hydrophobicity, and low bioavailability, affecting its anticancer effect, clinical applications of curcumin are highly limited. To enhance its performance in cancer therapies, some synergist approaches with curcumin have emerged. The present review presents some prospective ones (i.e. combinations with immunotherapy, chemotherapeutics, and bone tissue engineering materials) applied in osteosarcoma treatment. Additionally, with the advancements of photodynamic therapy in cancer therapy, this review also prospects the combination of curcumin with photodynamic therapy in osteosarcoma treatment.